2015
DOI: 10.1186/s12870-015-0662-7
|View full text |Cite
|
Sign up to set email alerts
|

Prospective function of FtsZ proteins in the secondary plastid of chlorarachniophyte algae

Abstract: BackgroundDivision of double-membraned plastids (primary plastids) is performed by constriction of a ring-like division complex consisting of multiple plastid division proteins. Consistent with the endosymbiotic origin of primary plastids, some of the plastid division proteins are descended from cyanobacterial cell division machinery, and the others are of host origin. In several algal lineages, complex plastids, the “secondary plastids”, have been acquired by the endosymbiotic uptake of primary plastid-bearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 75 publications
1
12
0
1
Order By: Relevance
“…We previously showed that some, but not all, nucleus-encoded chloroplast-division genes/proteins are specifically expressed in the S phase in a variety of algal lineages that possess chloroplasts of primary cyanobacterial endosymbiotic origin (11). In addition, cellcycle stage-specific expression of FtsZ mRNA was also reported in a diatom, which possesses chloroplasts of a secondary red algal endosymbiotic origin (32), and in a chlorarachniophyte alga, which possesses chloroplasts of a green algal secondary endosymbiotic origin (33). These studies suggest that the host cell restricts the onset of chloroplast division at a specific stage of the host cell cycle by the regulation of gene/protein expression.…”
Section: Discussionmentioning
confidence: 94%
“…We previously showed that some, but not all, nucleus-encoded chloroplast-division genes/proteins are specifically expressed in the S phase in a variety of algal lineages that possess chloroplasts of primary cyanobacterial endosymbiotic origin (11). In addition, cellcycle stage-specific expression of FtsZ mRNA was also reported in a diatom, which possesses chloroplasts of a secondary red algal endosymbiotic origin (32), and in a chlorarachniophyte alga, which possesses chloroplasts of a green algal secondary endosymbiotic origin (33). These studies suggest that the host cell restricts the onset of chloroplast division at a specific stage of the host cell cycle by the regulation of gene/protein expression.…”
Section: Discussionmentioning
confidence: 94%
“…Our previous studies have shown that a couple of nuclear genes for plastid- and nucleomorph-targeted proteins of B. natans were transcriptionally regulated under a diurnal cycle ( Hirakawa et al 2011 , Hirakawa and Ishida 2015 ). To obtain a comprehensive overview, we performed genome-wide transcript profiling using RNA-seq data along the B. natans cell cycles temporally synchronized by diurnal light and dark cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Through a poorly understood mechanism, FtsZ, along with components on the cytoplasmic 3 face of the chloroplast, then generates the contractile force required for membrane 3 constriction, and eventually, fission (Osawa et al, 2008). Recent work by Hirakawa et al 3 demonstrated the function of FtsZ proteins in the secondary plastid of chlorarachniophytes, 3 and in Bigelowiella natans, both FtsZD-1 and FtsZD-2 formed a ring-like structure that 3 bisected the midpoint of a bilobate pyrenoid found in the secondary chloroplast of this 3 species (Hirakawa & Ishida, 2015). This ring was constitutively present at this region and…”
mentioning
confidence: 96%